Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Kuhn, Jens H.; Becker, Stephan; Ebihara, Hideki; Geisbert, Thomas W.; Johnson, Karl M.; Kawaoka, Yoshihiro; Lipkin, W. Ian; Negredo, Ana I.; Netesov, Sergey V.; Nichol, Stuart T.; Palacios, Gustavo; Peters, Clarence J.; et al. (Archives of virology, 2010)
The taxonomy of the family Filoviridae (marburgviruses and ebolaviruses) has changed several times since the discovery of its members, resulting in a plethora of species and virus names and abbreviations. The current taxonomy has only been partially accepted by most laboratory virologists. Confusion likely arose for several reasons: species names that consist of several words or which (should) contain diacritical marks, the current orthographic identity of species and virus names, and the similar pronunciation of several virus abbreviations in the absence of guidance for the correct use of vernacular names. To rectify this problem, we suggest (1) to retain the current species names Reston ebolavirus , Sudan ebolavirus , and Zaire ebolavirus , but to replace the name Cote d’Ivoire ebolavirus [sic] with Taï Forest ebolavirus and Lake Victoria marburgvirus with Marburg marburgvirus ; (2) to revert the virus names of the type marburgviruses and ebolaviruses to those used for decades in the field (Marburg virus instead of Lake Victoria marburgvirus and Ebola virus instead of Zaire ebolavirus); (3) to introduce names for the remaining viruses reminiscent of jargon used by laboratory virologists but nevertheless different from species names (Reston virus, Sudan virus, Taï Forest virus), and (4) to introduce distinct abbreviations for the individual viruses (RESTV for Reston virus, SUDV for Sudan virus, and TAFV for Taï Forest virus), while retaining that for Marburg virus (MARV) and reintroducing that used over decades for Ebola virus (EBOV). Paying tribute to developments in the field, we propose (a) to create a new ebolavirus species ( Bundibugyo ebolavirus ) for one member virus (Bundibugyo virus, BDBV); (b) to assign a second virus to the species Marburg marburgvirus (Ravn virus, RAVV) for better reflection of now available high-resolution phylogeny; and (c) to create a new tentative genus ( Cuevavirus ) with one tentative species ( Lloviu cuevavirus ) for the recently discovered Lloviu virus (LLOV). Furthermore, we explain the etymological derivation of individual names, their pronunciation, and their correct use, and we elaborate on demarcation criteria for each taxon and virus.